2014
DOI: 10.1539/joh.13-0082-oa
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related Risk Factors for Workplace Violence among Korean Employees

Abstract: The aim of this study was to identify work-related risk factors for workplace violence in a representative sample of Korean employees. Methods: We analyzed the associations between work-related factors and workplace violence in 29,171 employees using data from the 2011 Korean Working Conditions Survey. The survey included questions about verbal abuse, unwanted sexual attention, threats and behavior that humiliated the victim, physical violence, bullying/harassment and sexual harassment, and a respondent who an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 36 publications
6
29
2
Order By: Relevance
“…In this study, only 34.3% of the violent episodes were reported to a supervisor, this being a common finding reported by researchers 2,32,33) when studying WPV in general. A study of nurses in the Canadian provinces of Alberta and British Columbia also showed underreporting of aggressive behaviors, with only 30% being reported, as in our study 33) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, only 34.3% of the violent episodes were reported to a supervisor, this being a common finding reported by researchers 2,32,33) when studying WPV in general. A study of nurses in the Canadian provinces of Alberta and British Columbia also showed underreporting of aggressive behaviors, with only 30% being reported, as in our study 33) .…”
Section: Discussionsupporting
confidence: 55%
“…First, in studying the prevalence of WPV and its determinants, several researchers 32) have reported that it is difficult to compare and contrast statistics from different countries for several reasons, such as the discrepancy in the concepts being studied, inconsistencies in the methods used and cultural differences in the experience of violence 32) . As we could not find previously published research in the literature regarding WPV in the DRC, our findings were therefore cautiously compared with studies in countries where health-care systems, workplace environment, and cultural background regarding the understanding of verbal violence and harassment might be different from those of the DRC; examples of such differences include male nurses working in the female patient wards, wartime conditions in the country and cultural differences relating to the understanding of verbal violence or harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other Asian countries have indicated that nurses are at alarmingly high risk for workplace violence, with a one‐year prevalence ranging from 25.8% to 95.5% (Cheung & Yip, ; Choi & Lee, ; Sun et al., ; Zhang et al., ). However, few studies examined the impact of organisational psychosocial safety climate on workplace violence and workers’ health (Courcy, Morin, & Madore, ; Lee, Kim, & Park, ; Sun et al., ), and only two studies have used PSC scale in the Asian population (Idris & Dollard, ; Idris et al., ). Industrial safety climate and health promoting efforts varies widely across countries, but they were found to be worse in Taiwan than most Western countries (Cheng, ; Li, Harris, & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from other Asian countries have indicated that nurses are at alarmingly high risk for workplace violence, with a one-year prevalence ranging from 25.8% to 95.5% (Cheung & Yip, 2017;Choi & Lee, 2017;Sun et al, 2017;Zhang et al, 2017). However, few studies examined the impact of organisational psychosocial safety climate on workplace violence and workers' health (Courcy, Morin, & Madore, 2016;Lee, Kim, & Park, 2014;Sun et al, 2017), and only two studies have used PSC scale in the Asian population .…”
Section: Introductionmentioning
confidence: 99%
“…While mobbing mainly focuses on criticisms and rumors concerning the private life in women, it often concentrates on work performance in men [1]. Other authors described risk factors for workplace mobbing such as occupational status (people with higher levels of education tend to have lower alert thresholds to negative situations [1]), long working hours, job insecurity, and night shift work [39], [41]. As found by Klomek at al.…”
Section: Discussionmentioning
confidence: 99%